Geographical range in liverworts: does sex really matter?. (4th November 2015) - Laenen, Benjamin; Machac, Antonin; Gradstein, S. Robbert; Shaw, Blanka; Patiño, Jairo; Désamoré, Aurélie; Goffinet, Bernard; Cox, Cymon J.; Shaw, Jonathan; Vanderpoorten, Alain
Abstract: Aim: Why some species exhibit larger geographical ranges than others remains a fundamental, but largely unanswered, question in ecology and biogeography. In plants, a relationship between range size and mating system was proposed over a century ago and subsequently formalized in Baker's Law. Here, we take advantage of the extensive variation in sexual systems of liverworts to test the hypothesis that dioecious species compensate for limited fertilization by producing vegetative propagules more commonly than monoecious species. As spores are assumed to contribute to random long‐distance dispersal, whereas vegetative propagules contribute to colony maintenance and frequent short‐distance dispersal, we further test the hypothesis that monoecious species exhibit larger geographical ranges than dioecious ones. Location: Worldwide. Methods: We used comparative phylogenetic methods to assess the correlation between range size and life history traits related to dispersal, including mating systems, spore size and production of specialized vegetative propagules. Results: No significant correlation was found between dioecy and production of vegetative propagules. However, production of vegetative propagules is correlated with the size of geographical ranges across the liverwort tree of life, whereas sexuality and spores size are not. Moreover, variation in sexual systems did not have an influence on the correlation between geographical range and production of asexual propagules. Main conclusions: Our results challenge the long‐held notion that spores, and not vegetative propagules, are involved in long‐distance dispersal. Asexual reproduction seems to play a major role in shaping the global distribution patterns of liverworts, so that monoecious species do not tend to display, on average, broader distribution ranges than dioecious ones. Our results call for further investigation on the spatial genetic structure of bryophyte populations at different geographical scales depending on their mating systems to assess the dispersal capacities of spores and asexual propagules and determine their contribution in shaping species distribution ranges.